חילון ואוריינטליזם ביחסי הסופר המזרחי והביקורת: יהודה בורלא המוקדם כמקרה מבחן - דותן קרן (מכאן, 2020)
This article investigates Hebrew literary critism in Eretz-Israel in the beginning of the 20th century, when the local literary center strove to establish itself as a cultural and political alternative to the exilic literary centers in Europe, and was haunted by questions of sovereignty, locality, and Mizrahiness. The article looks into the discourse on Mizrahi writing and its attempt to conceptualize the differences (i.e. to answer the question: "What makes Mizrahi writing different than general writing?") through various categories such as "inner essence", "realism", "exile" and "psychology". In particular, it demonsrates the role of the literary form in creating an overlap between Orientalist elements of the local literature and its ambition to form itself as secular. Finally, these processes are discussed in detail through a close reading of the novel In Darkness Striving (Neftulei Adam).